Overcoming trastuzumab resistance in HER2‐positive breast cancer using combination therapy - Derakhshani, Afshin; Rezaei, Zohreh; Safarpour, Hossein; Sabri, Morteza; Mir, Atefeh; Sanati, Mohammad Amin; Vahidian, Fatemeh; Gholamiyan Moghadam, Ali; Aghadoukht, Ali; Hajiasgharzadeh, Khalil; Baradaran, Behzad (Journal of cellular physiology, 2020)
Human epidermal growth factor receptor 2 (HER2)‐positive breast cancer (BC) comprises around 20–30% of all BC subtypes and is correlated with poor prognosis. For many years, trastuzumab, a monoclonal antibody, has been used to inhibit the HER2 activity. Though, the main resistance to trastuzumab has challenged the use of this drug in the management of HER2‐positive BC. Therefore, the determination of resistance mechanisms and the incorporation of new agents may lead to the development of a better blockade of the HER family receptor signaling. During the last few years, some therapeutic drugs have been developed for treating patients with trastuzumab‐resistant HER2‐positive BC that have more effective influences in the management of this condition. In this regard, the present study aimed at reviewing the mechanisms of trastuzumab resistance and the innovative therapies that have been investigated in trastuzumab‐resistant HER2‐positive BC subjects. Human epidermal growth factor receptor 2 (HER2)‐positive breast cancer (BC) comprises around 20–30% of all BC subtypes and is correlated with poor prognosis. During the last few years, some therapeutic drugs have been developed for treating patients with trastuzumab‐resistant HER2‐positive BC that have more effective influences in the management of this condition. So, the present study aimed at reviewing the mechanisms of trastuzumab resistance and the innovative therapies that have been investigated in trastuzumab‐resistant HER2‐positive BC subjects.